Students' Language Poetty In Social Media In Indonesian Online Learning - Kusyairi; Ratna Sari; Sofiea Anggraini (Demagogi: Journal of Social Sciences, Economics and Education, 2024)
Language politeness is one of the key aspects of a person's success in establishing social relationships. This research, which examines language politeness on social media, aims to describe how polite students should have, both in communicating with teachers and with their peers. In general, attitude can be assessed through the intonation and direct expression of the speaker. Meanwhile, on social media, these two elements are not visible in expressions that only consist of writing or chat. In its method, this research uses a qualitative descriptive method. Data collection techniques are reading and note-taking techniques. Meanwhile, the data analysis technique used in this research is an interactive model, namely data collection, (2) data reduction, (3) data presentation, and (4) drawing conclusions.